اسلامی حدود: دائرۂ عمل اور منہجِ تنفیذ: Islamic capital punishments: Scope and Implementation procedure (Al-Qamar, 2021)
These punishments prescribed by the religion of Islam are very just, at the same time they are in the interest of the people, human dignity, mutual respect, destruction of the family system, corruption of lineage, encroachment on people's property, abuse of human beings. To maintain the intellect and the ability to think and understand, to prevent many corruptions and evils, to cleanse society from crime and to establish and maintain public order. As the rain brings prosperity, the fields sway. The life of such subjects depends on the enforcement of Islamic punishments. The punishments for the crimes prescribed by the Qur'an and Sunnah are called (extreme crimes). These are adultery, slander and slander, stealing, drinking, fighting and apostasy. The punishment of adultery (in Islam) is for a virgin i.e., for both male and female to be hastened, while for those who are married it is to be stoned. The punishment for making false accusations and slanders is to inflict the same blows. The Shariah punishment for theft is hand-wringing. The penalty for alcoholism is 40 lashes or 40 or 80 lashes. Muharrabat means killing, hanging, deportation or amputation of hands and feet in the opposite direction for causing mischief in the land and the punishment for apostasy is murder. This will eradicate crime and disobedience and will save the life, property, honor and dignity of everyone. Love, compassion and brotherhood grow among each other. As a result, the earth spews out its treasures. And the rain of mercy falls from the sky. Hudud should not be recommended. Personal and spatial determination should be taken into consideration for the removal of Hudud. Doubts should be taken into consideration.
Keywords: Punishments; Islam; Just; Dignity; Mutual respect; corruption of lineage; Evils; crime fiction in Arabic; Qur’an & Sunnah; Slander and Slander; Accusations; Killing; Deportation; consideration